PERBEDAAN KEKERASAN ANTARA FIBER REINFORCED COMPOSITE DENGAN FIBER SISAL (Agave sisalana) TERALKALISASI DAN NON-ALKALISASI - , SAWITRI TRISNANINGTYAS, Prof. Dr. drg. Widjijono, S.U. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Fiber reinforced composite (FRC) is a material composed of matrix and fiber as reinforcing material. Fiber reinforced composite has been used for fixed partial dentures in dental application. Sisal fiber is currently used more and more as reinforcing material on FRC. Hardness is one of important properties in dental materials. Alkalization is one of such treatments that can increase hardness. This research aimed to determine the difference between the FRC with alkalized sisal fiber and the non-alkalized one. The research material used was FRC with flowable composite resin matrix (Master Flow, Brazil) and sisal fiber (Balittas, Indonesia). Alkalization was carried out by soaking the fiber in 5% NaOH solution for 4 hours which was then dried in an oven for 24 hours at a temperature of 80oC. The research sample took form of a block with a size of 2x2x25mm. It was cured with a light curing unit for 20 seconds. The number of samples was 8 and they were divided into 2 groups, the alkalized and the non-alkalized (n=4). Samples were stored in distilled water for 24 hours at a temperature of 37oC. Hardness was measured using Vickers hardness tester with the load of 25 grams for 10 seconds. Data of hardness was then analyzed statistically using independent t-test (Î±=0.05). The results showed that mean of hardness of the FRC group with alkalized sisal fiber was 106.04 Â± 1.36 VHN and that with non-alkalized sisal fiber was 52.66 Â± 1.84 VHN. Independent t-test result indicated that there was significant difference of hardness between the FRC with alkalized sisal fiber and the one with nonalkalized sisal fiber (p<0.05). The conclusion of this research was alkalization can increase hardness of the FRC with sisal fiber (Agave sisalana).